MANAGEMENT OF TEACHER PERFORMANCE APPRAISAL IN ACEH BARAT DAYA JUNIOR HIGH SCHOOLS - Chika Fradilla; Murniati AR; Khairuddin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to analyze the management of teacher performance appraisal in public junior high schools (SMP Negeri) in Aceh Barat Daya. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The research subjects include supervisors, principals, and teachers at SMPN 1 Susoh and SMPN 1 Setia. The results showed that: (1) Planning for teacher performance appraisal is carried out at the end of the academic year involving school supervisors, principals, senior teachers, subject teachers, and the school quality development team. Planning includes evaluating teacher discipline, reviewing learning administration, and teacher performance improvement programs. (2) The implementation of teacher performance appraisal is carried out annually by supervisors and principals by evaluating teacher reports, checking attendance, teaching administration, and implementing strategies for discipline development and teacher competency improvement. (3) Supervision of teacher performance appraisal is carried out by principals and supervisors in monitoring problems, discipline, and the availability of teacher instruments to improve professionalism and education quality. (4) Supporting factors for teacher performance appraisal include teacher qualifications, skills, motivation and personality, while inhibiting factors include curriculum changes, limited infrastructure, and time management that is not yet optimal.